Chronic demyelinating polyneuropathy associated with anti-ganglioside GQ1b antibodies in peripheral T-cell lymphoma - Salem Bahashwan; Carolyne Croizier; Xavier Moisset; Romain Guièze; Bertrand Evrard; Olivier Tournilhac; Jacques-Olivier Bay; Richard Lemal (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2019)
Malignant lymphoma can cause peripheral neuropathy through various mechanisms. We report the case of 67-year-old man with chronic motor and sensory axonal demyelinating polyneuropathy associated with anti-ganglioside GQ1b antibodies in serum and cerebrospinal fluid (CSF) as an initial presentation of peripheral T-cell lymphoma, not otherwise specified. The patient was treated with chemotherapy for T-cell lymphoma, and achieved complete remission.  Motor function recovered completely and sensory function improved. Neurological improvement was concurrent with the disappearance of serum and CSF anti-ganglioside GQ1b antibodies. This is the first report of chronic demyelinating polyneuropathy associated with anti-ganglioside GQ1b antibodies in peripheral T-cell lymphoma.